2004
DOI: 10.1128/iai.72.1.247-252.2004
|View full text |Cite
|
Sign up to set email alerts
|

Association between Protection against Clinical Malaria and Antibodies to Merozoite Surface Antigens in an Area of Hyperendemicity in Myanmar: Complementarity between Responses to Merozoite Surface Protein 3 and the 220-Kilodalton Glutamate-Rich Protein

Abstract: We performed a longitudinal clinical and parasitological follow-up study in OoDo, a village in southeast Asia in which malaria is hyperendemic, in order to assess the association between protection against malaria attacks and antibodies to three currently evaluated vaccine candidates, merozoite surface protein 1 (MSP1), MSP3, and the 220-kDa glutamate-rich protein (GLURP) from Plasmodium falciparum. Our results showed that the levels of cytophilic immunoglobulin G3 (IgG3) antibodies against conserved regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
125
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 31 publications
(28 reference statements)
21
125
0
4
Order By: Relevance
“…Similarly, high antibody levels of MSP-1 specific IgG1 were associated with reduced morbidity (Riley et al, 1992;Al-Yaman et al, 1996) with protection against high-level parasitemia (Fowkes et al, 2010) and clinical disease (Egan et al, 1996;Cavanagh et al, 2004;Soe et al, 2004).…”
Section: The Role Of Msp-1 In Natural Immunitymentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, high antibody levels of MSP-1 specific IgG1 were associated with reduced morbidity (Riley et al, 1992;Al-Yaman et al, 1996) with protection against high-level parasitemia (Fowkes et al, 2010) and clinical disease (Egan et al, 1996;Cavanagh et al, 2004;Soe et al, 2004).…”
Section: The Role Of Msp-1 In Natural Immunitymentioning
confidence: 97%
“…Evidence from field studies in Ghana (Dodoo et al, 2000), Senegal (Oeuvray et al, 2000) and East Asia (Soe et al, 2004) suggest that cytophilic antibodies are associated with a lower risk for subsequent clinical malaria episodes. These isotypes are also associated with the antibody-dependent cellular inhibition as discussed above.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…As a novel alternative to cope with this situation, multistage vaccines have been designed in an attempt to interrupt the life cycle in both vertebrate and invertebrate hosts. Using antigens from blood stages as the glutamate-rich protein (GLURP) that had been recognized as a natural antigen in acquiring immunity against malaria [82] and by the usage of sexual stage antigens Pfp48/45 that are involved in gamete fusion during sexual reproduction within the mosquito vector [83], the central objective of this alternative multiepitope vaccine is to confer immunity in the people that is at risk to acquire the infection and to reduce in long term the infection in the vector avoiding transmission [84]. The usage of more than two antigens is also an opportunity to confer immunity against parasites and to ensure the success to block the infection.…”
Section: New Strategies Against Apicomplexan Parasitesmentioning
confidence: 99%
“…These immunogens are МSP-3-LSP (Long synthetic protein) that represents the МSP-3 fragment including the residues 186-276  Bouharoun-Tayoun, 1995 and GLURP-LPS that represents the GLURP fragment including the residues 85-213 (Dodoo et al, 2000;Theisen et al, 2000Theisen et al, , 2001. These peptide immunogens were highly conservative for all plasmodium isolates; they induced formation of cytophilic antibodies of IgG1 and IgG3 subclasses; via opsonizing shizonts they attracted monocytes that caused shizont lysis (Theisen et al, 2001;Soe et al, 2004). Phase I clinical trials (Druilhe et al, 2005;Sirima et al, 2009) demonstrated formation of long (at least 1 year) immune response to these vaccines.…”
Section: Peptide Vaccines Against Malariamentioning
confidence: 99%